Electrochemical assessment of magnetite anticorrosive paints (2003)
With the purpose of deepening in the understanding of the mechanisms of protection of anticorrosive pigments based on iron oxides, this work has been carried out on the production of pure magnetite, and copper and chromium doped magnetite, which were evaluated by different characterization techniques. The paints were prepared with a solvent less epoxy resin maintaining the Pigment Volume Content near the Practical Critical value (CPVC), established for each pigment. The paints were applied on polished steel and monitored with electrochemical techniques at total immersion conditions. Permeability and impedance measurements of free films were also done. Impedance data were simulated with the Boukamp software. Results show that the paints pigmented with doped magnetite present better behavior than a paint prepared with commercial hematite.